Modelling and supporting flight crew decision-making during aircraft engine malfunctions: developing design recommendations from cognitive work analysis - Asmayawati, Saryani; Nixon, Jim (Elsevier, 2019)
In this article, we analyse flight crew response to an in-flight powerplant system malfunction (PSM) using control task analysis. We demonstrate the application of the decision ladder template and the skills, rules, and knowledge (SRK) framework to this new area of inquiry. Despite the high reliability of turbofan engines, accidents and incidents involving PSM still occur. During these unusual events, flight crew have not always responded appropriately, leading to a reduction in safety margins or disruption of operations. This article proposes recommendations for technological and information system that can support flight crew in responding safely and appropriately to a PSM. These recommendations focus on new ways in which information from engine health monitoring system and other sources of data can be utilised and displayed. Firstly, we conducted knowledge elicitation using Critical Decision Method (CDM) interviews with airline pilots who have experienced real or simulated PSM events. We then developed generic decision ladders using the interview data, operations manual, training manual, and other guideline documents. The generic decision ladders characterise the different stages of responding to PSM identified as part of the research. These stages include: regaining and maintaining control of aircraft, identifying PSM and selecting appropriate checklists to secure the engine, and modifying the flight plan. Using the decision ladders and insights from the CDM interviews, we were able to identify cognitive processes and states that are more prone to errors and therefore more likely to generate an inappropriate response. Using the SRK framework, we propose design recommendations for technological and information systems to minimise the likelihood of such inappropriate response. We conclude that this combination of methods provides a structured and reliable approach to identifying system improvements in complex and dynamic work situations. Our specific contributions are the application of these techniques in the unrepresented area of flight operations, and the development of evidence-based design recommendations to improve flight crew response to in-flight powerplant system malfunctions.
Keywords: Cognitive work analysis; Flight crew decision-making; Aircraft engine malfunction